2012
DOI: 10.1021/jf301361c
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Bioactive Pro-Peptides with in Vitro Renin Inhibitory Activities from the Macroalga Palmaria palmata

Abstract: Renin is the initial rate limiting step in the renin angiotensinogen system (RAS). To combat hypertension, various stages of the RAS can be positively affected. The aim of this study was to isolate and characterize renin inhibitory peptides from the red seaweed P. palmata for use in functional foods. Palmaria palmata protein was extracted and hydrolyzed with the food grade enzyme Papain to generate renin inhibitory peptides. Following proteolytic hydrolysis of P. palmata protein, reverse phasehigh performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
91
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(98 citation statements)
references
References 25 publications
6
91
1
Order By: Relevance
“…Multifunctional peptides with both ACE-and renin-inhibitory activities have also been identified from plant food sources like peanut, flaxseed, pea, hemp seed, soy sauce and red seaweed (Fitzgerald et al, 2012;Jamdar et al, 2010;Jimsheena & Gowda, 2010;Rho, Lee, Chung, Kim & Lee, 2009;). Identification of antihypertensive agents or bioactive substances that possess both renin and ACEinhibitory activities has currently become an important research focus since the control of ACE alone does not completely prevent production of Angiotensin II, the vasoconstrictor which is continually produced from an ACE independent pathway catalyzed by chymase.…”
Section: Figure 22 Possible Mechanisms Of Action Of Bioactive Peptidmentioning
confidence: 99%
See 1 more Smart Citation
“…Multifunctional peptides with both ACE-and renin-inhibitory activities have also been identified from plant food sources like peanut, flaxseed, pea, hemp seed, soy sauce and red seaweed (Fitzgerald et al, 2012;Jamdar et al, 2010;Jimsheena & Gowda, 2010;Rho, Lee, Chung, Kim & Lee, 2009;). Identification of antihypertensive agents or bioactive substances that possess both renin and ACEinhibitory activities has currently become an important research focus since the control of ACE alone does not completely prevent production of Angiotensin II, the vasoconstrictor which is continually produced from an ACE independent pathway catalyzed by chymase.…”
Section: Figure 22 Possible Mechanisms Of Action Of Bioactive Peptidmentioning
confidence: 99%
“…Recently, quite a number of antihypertensive peptides with multi-functional properties capable of inhibiting ACE and renin enzymes in vitro and in vivo conditions have been produced from various plant and animal food sources. Peptides with dual ability to inhibit ACE and renin have through enzymatic hydrolysis been identified from seaweeds (Fitzgerald et al, 2012), yellow field pea seeds , flaxseed ), rapeseed and hemp seed . Li et al…”
Section: Introductionmentioning
confidence: 99%
“…For instance, limited research has focused on edible macroalgal proteins, which then represent a great potential for bioactive peptide generation (Harnedy & FitzGerald, 2011, 2013aHeo, Park, Lee, & Jeon, 2005). Studies using proteolytic enzyme hydrolysis demonstrated the presence of bioactive peptides from the red macroalga Palmaria palmata, which exhibited in vitro cardioprotective, anti-diabetic, antioxidant, Angiotensin converting enzyme (ACE) inhibition potential (Harnedy & FitzGerald, 2013b;Harnedy, Soler-Vila, Edwards, & FitzGerald, 2014) and renin inhibitory activities (Fitzgerald et al, 2012). Cian, Alaiz, Vioque, and Drago (2013) and Cian, Martinez-Augustin, and Drago (2012) have reported protein hydrolysate extracts of the red macroalga Pyropia (Porphyra) columbina, which displayed both in vitro ACE inhibitory and antioxidant properties (Cian et al, 2012(Cian et al, , 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Yua, Yin, Zhao, Liu and Chen, (2012) evaluated and validated the anti-diabetic activity of bioactive peptides from albumin against α-glucosidase and α-amylase. Fitzgerald et al (2012) has also isolated and characterized bioactive Pro-Peptides with in vitro Renin inhibitory activities from the Macro algae Palmaria palmata. Thus far, there appears to be limited information regarding to α-amylase inhibition activity by seaweed protein derived-hydrolysates /peptides.…”
Section: Introductionmentioning
confidence: 99%